2003
DOI: 10.1097/01.mp.0000044621.08865.c4
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Molecular Alterations Present in Stage I Non-Small Cell Lung Carcinoma Fail to Predict Tumor Recurrence

Abstract: Stage I non-small cell carcinoma (NSCLC) of the lung is typically treated with surgery alone, but with a 30 to 40% recurrence rate. Prognostic factors to stratify these patients into high-and low-risk groups would be of significant clinical value, but published data are conflicting. We studied 39 Stage I NSCLC treated with resection alone, followed for a minimum of 5 years, and divided into recurrent (RC) and non-recurrent (NRC) groups (n ‫؍‬ 12 and 27, respectively). Allelic imbalance (loss of heterozygosity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…Unlikely other studies that enrolled only stage I NSCLC patients [1,25], the present study includes stage I-IV tumours.…”
Section: Discussionmentioning
confidence: 96%
“…Unlikely other studies that enrolled only stage I NSCLC patients [1,25], the present study includes stage I-IV tumours.…”
Section: Discussionmentioning
confidence: 96%
“…Certainly, a larger number of patients should be analysed to corroborate or disprove this assumption. Concerning the prognostic value of molecular alterations in the literature, conflicting results have been reported (66)(67)(68).…”
Section: ------------------------------------------------mentioning
confidence: 96%
“…KRAS mutations were a significant predictor of tumor recurrence in 244 NSCLCs (45), but not in two smaller studies (40,46). A recent metaanalysis of 28 studies in NSCLC revealed a significant association between KRAS mutation and poorer survival in adenocarcinomas, but not SCCs (43).…”
Section: Discussionmentioning
confidence: 99%